Patient assessment of treatment satisfaction: methods and practical issues. (13th April 2004) - Revicki, D A
Abstract : Measurement of treatment satisfaction in gastro-oesophageal reflux disease (GORD) is compromised by an insufficient conceptual foundation and poor assessment methods. The current state of the art in measuring treatment satisfaction is incomplete, and the existing measurement is insufficient. Here, the definition, conceptualisation, application, and methodological issues associated with measurement of treatment satisfaction in GORD are reviewed. Treatment satisfaction may be important for differentiating among GORD treatments, and for monitoring patient outcomes in clinical practice.